The water effect on allosteric regulation of hemoglobin probed in water glucose and water glycine solutions - Colombo, M. F.; BonillaRodriguez, G. O. (Amer Soc Biochemistry Molecular Biology Inc, 1996)
We have previously proposed a role of hydration in the allosteric control of hemoglobin based on the effect of varying concentrations of polyols and polyethers on the human hemoglobin oxygen affinity and on the solution water activity (Colombo, M. F., Rau, D. C., and Parsegian, V. A. (1992) Science 256, 655-659). Here, the original analyses are extended to test the possibility of concomitant solute and water allosteric binding and by introducing the bulk dielectric constant as a variable in our experiments.We present data which indicate that glycine and glucose influence HbA oxygen affinity to the same extent, despite the fact that glycine increases and glucose decreases the bulk dielectric constant of the solution. Furthermore, we derive an equation linking changes in oxygen affinity to changes in differential solute and water binding to test critically the possibility of neutral solute heterotropic binding. Applied to the data, these analyses support our original interpretation that neutral solutes act indirectly on the regulation of allosteric behavior of hemoglobin by varying the chemical potential of water in solution. This leads to a displacement of the equilibrium between Hb conformational states in proportion to their differential hydration.